Consistent Plant and Microbe Nutrient Limitation Patterns During Natural Vegetation Restoration - Xue, Yue; Kang, Haibin; Cui, Yongxing; Lu, Sheng; Yang, Hang; Zhu, Jiaqi; Fu, Zhenjie; Yan, Chenglong; Wang, Dexiang (Frontiers in Plant Science, 2022)
Vegetation restoration is assumed to enhance carbon (C) sequestration in terrestrial ecosystems, where plant producers and microbial decomposers play key roles in soil C cycling. However, it is not clear how the nutrient limitation patterns of plant and soil microbe might change during vegetation restoration. We investigated the nutrient limitations of the plant and microbial communities along a natural vegetation restoration chronosequence (1, 8, 16, 31, and 50 years) following farmland abandonment in Qinling Mountains, China and assessed their relationships with soil factors. The result showed that following natural vegetation restoration, the nitrogen (N) limitation of plant and microbial communities alleviated significantly and thereafter began to shift to phosphorus (P) limitation at the later stage. Plant showed P limitation in 50 years after restoration while microbial P limitation appeared in 31 years. The changes in plant nutrient limitation were the consistent of those in microbial nutrient limitation, but soil microbes were limited by P earlier than plants.. Random forest model and partial least squares path modelling revealed that soil nutrient stoichiometry, especially soil C:N ratio, explained more variations for changes in plant and microbial nutrient limitation. Our study demonstrates that the imbalanced of soil C:N ratio may determine the soil microbial metabolic limitation and further mediate the variation in plant nutrient limitation during natural vegetation restoration, which provides important insights into the link between metabolic limitation for microbes and nutrient limitation for plants during vegetation restoration to improve our understanding of soil C turnover in temperate forest ecosystems.